1998
DOI: 10.1063/1.368066
|View full text |Cite
|
Sign up to set email alerts
|

Measurements and comparison of low frequency noise in npn and pnp polysilicon emitter bipolar junction transistors

Abstract: Monte Carlo analysis of the noise behavior in Si bipolar junction transistors and SiGe heterojunction bipolar transistors at radio frequencies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Note again that the two terms for coupled (Δn, let's say) and intrinsic (Hooge) fluctuations in equations (11) and (12) present different sides and origins for the low-frequency noise in the current transport, and they do not contradict each other. Also, the normalized noise S norm , as defined with these equations, is a power spectrum density with a unit Hz -1 , and is a convenient figure of merit, which estimates the noise "power" per a bandwidth of 1 Hz in ratio to the DC "power", that can be obtained by multiplying the nominator and denominator of the equations with the resistance of the device.…”
Section: Ii3 Combination Of Coupled and Intrinsic Fluctuationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Note again that the two terms for coupled (Δn, let's say) and intrinsic (Hooge) fluctuations in equations (11) and (12) present different sides and origins for the low-frequency noise in the current transport, and they do not contradict each other. Also, the normalized noise S norm , as defined with these equations, is a power spectrum density with a unit Hz -1 , and is a convenient figure of merit, which estimates the noise "power" per a bandwidth of 1 Hz in ratio to the DC "power", that can be obtained by multiplying the nominator and denominator of the equations with the resistance of the device.…”
Section: Ii3 Combination Of Coupled and Intrinsic Fluctuationsmentioning
confidence: 99%
“…The areal dependence with increasing normalized noise in npn BJTs with smaller emitter area A E is shown in Figure 2, using the SPICE parameter K F defined from The data for more than 150 devices are collected from [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27], and shown in Figure 2 with some points omitted for clarity. Since the numbers spread over several decades, we use geometric averaging technique [28] to extract the trend in the data from the product A E ×K F ; and the trend is A E ×K F ≈5.6×10 -9 µm 2 with logarithmic standard deviation of σ dB =3.4dB.…”
Section: Noise In Bjtmentioning
confidence: 99%
See 2 more Smart Citations
“…With new technology, the size of transistors is reduced which gives high current and high-frequency gain but also increase low-frequency noise [106]. In a study by [107], it was observed that, in NPN transistors, shot noise of the base current contributes to total noise, while in a PNP transistor, generation-recombination noise adds to the total noise. Because of high mobility of electrons, NPN transistors have high conductivity and thus, switching time in NPN transistors is faster than that of in PNP transistors.…”
Section: Transistorsmentioning
confidence: 99%